2022
DOI: 10.3390/bioengineering9100512
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in CRISPR/Cas-Based Biosensors for Protein Detection

Abstract: CRISPR is an acquired immune system found in prokaryotes that can accurately recognize and cleave foreign nucleic acids, and has been widely explored for gene editing and biosensing. In the past, CRISPR/Cas-based biosensors were mainly applied to detect nucleic acids in the field of biosensing, and their applications for the detection of other types of analytes were usually overlooked such as small molecules and disease-related proteins. The recent work shows that CRISPR/Cas biosensors not only provide a new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…State-of-the-art electrochemical bioplatforms have been developed by using CRISPR/Cas systems as biorecognition elements for single or multiplexed determination of nucleic acids, or as signal amplifiers to interrogate nucleic acids or other analytes such as proteins, metals, and bacteria. Indeed, the versatility of modern electrochemical platforms and instrumentation involving CRISPR/Cas technologies allow the determination of markers of different molecular levels and the development of multiplexed electrochemical bioplatforms.…”
Section: Key Alliances To Cover Important Routesmentioning
confidence: 99%
“…State-of-the-art electrochemical bioplatforms have been developed by using CRISPR/Cas systems as biorecognition elements for single or multiplexed determination of nucleic acids, or as signal amplifiers to interrogate nucleic acids or other analytes such as proteins, metals, and bacteria. Indeed, the versatility of modern electrochemical platforms and instrumentation involving CRISPR/Cas technologies allow the determination of markers of different molecular levels and the development of multiplexed electrochemical bioplatforms.…”
Section: Key Alliances To Cover Important Routesmentioning
confidence: 99%
“…LbCas12a protein binding to Protospacer adjacent motif directly leads to local melting of PAM downstream target sequence DNA, causing downstream sequence complementation with speci cally recognized gRNA, thereby activating cleavage of target DNA by Cas12a protein [23]. The activity of the Cas12a protein directly affects the detection e cacy of the CRISPR/Cas12a system.…”
Section: Validation Of Cleavage Activity Of Lbcas12a Proteinmentioning
confidence: 99%
“…The results showed that the fluorescence bioassay based on CRISPR-Cas12a is able to accurately distinguish people with cancer from healthy ones. [189]…”
Section: Crispr As a Tool For Diagnosismentioning
confidence: 99%
“…They found that the CRISPR‐Cas12a‐based fluorescence bioassay against mismatched sequences had a high specificity as well as a high sensitivity of about 161 fM for the determination of miR‐21. The results showed that the fluorescence bioassay based on CRISPR‐Cas12a is able to accurately distinguish people with cancer from healthy ones [189] …”
Section: Crispr‐cas 9 Systems: Components and Limitationsmentioning
confidence: 99%